La Comèdia de la General Conquista de Mallorca en relació amb el context cultural del sis-cents. - DARDER-MOLL, AUGUST (Scripta, 2017)
In the article we analyse a Majorcan theatre piece entitled Comèdia de la General Conquista de Mallorca that was written at the end of the seventeenth century. About the author we only know his name, Pere Antoni Bernat. We wanted to put this work in relation to the sociocultural environment of its time, and to do so we have focused on four main aspects: the contextual one, in order to see the conditions that could have favoured the creation of a work with such characteristics; the historical one, for which we have fixed on the Comèdia's contents related to some historiographical works; the formal one, which includes the influences of contemporary literature that we have been able to trace in the work and the ideological one, which consists in an analysis of the values that the work transmits.